Zeolitic Imidazolate Framework Film Derived CoFe‐N‐C Nanofoams for Reliable Zn‐air Batteries. Issue 4 (4th December 2022) - Zhang, Junfeng; Liu, Haotian; Zhu, Weikang; Chen, Bin; Yue, Runfei; Yin, Shuoyao; Xie, Na; Li, Ran; Yin, Yan
Abstract: The design of the efficient, flexible air electrode for enhancing the Zn‐air batteries (ZABs) performance is vital in developing a new portable rechargeable power supply. Emerging research indicates that non‐precious metal materials have promising activity for oxygen reduction/evolution in alkaline conditions while constructing a high‐performance and reliable electrode is still a big challenge at the present stage. In this work, a bimetal doped zeolitic imidazolate framework (ZIF) film is synthesized by fast current‐driven synthesis (FCDS) on a thin carbon nanotube film (CNTF). After carbonization at 950 °C, CoFe‐N‐C nanofoam formed on the CNTF, resulting in binder‐free, flexible electrodes. It exhibits excellent activity and stability toward oxygen reduction and evolution. The CoFe‐N‐C/CNTF‐based liquid‐state ZAB shows an output power density of 294 mW cm −2 . When applied in solid‐state ZAB, the flexible battery shows high power density and excellent cycling stability. Abstract : A flexible CoFe‐based carbon nanotube film is synthesized by fast current‐driven synthesis and the high‐temperature pyrolysis method. It exhibits a high power density of 294 mW cm −2, high specific capacity of 772 mAh gZn −1, and excellent reversibility of discharge and charge during the Zn‐air battery application.